Disaster risk management - May, Jutta (Technical Centre for Agricultural and Rural Cooperation, 2013)
Pacific Disaster Net is one of several initiatives that brings together a wide selection of information and tools that supports stakeholders and communities to prepare for and manage natural disasters in the Pacific island region